ANALISIS DAYA PEMBEDA BUTIR TES PILIHAN GANDA MATERI PERSAMAAN TRIGONOMETRI BERDASARKAN TEORI TES KLASIK - Rizki, Ahmad; Halini, Halini; Indriani, Tari (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
This study aims to measure the distinguishing power of the multiple-choice form test items of class XI trigonometric equation material at SMA Mujahidin Pontianak. The object analyzed is 40 items of multiple-choice questions of trigonometric equation material. The type of research used is descriptive quantitative. The data collection method is a documentation method and the data obtained in the form of secondary data is then analyzed using a classical test theory approach. The results of the analysis showed that as many as 7 questions or 20.59% had bad distinguishing power criteria, 16 questions or 47.06% had sufficient discriminating power, 10 questions or 29.41% had good discriminating power criteria, 1 question or 2.94% had bad discriminating power, and no questions or as many as 0% had very good discriminating power. From the overall data, it can be concluded that the test items have a differentiating power that meets the feasible criteria because most of the questions have sufficient criteria.